2013
DOI: 10.1051/0004-6361/201321300
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gaps in flaring Herbig Ae/Be disks using spatially resolved mid-infrared imaging

Abstract: Context. The evolution of young massive protoplanetary disks toward planetary systems is expected to correspond to structural changes in observational appearance, which includes the formation of gaps and the depletion of dust and gas. Aims. A special group of disks around Herbig Ae/Be stars do not show prominent silicate emission features, although they still bear signs of flaring disks, the presence of gas, and small grains. We focus our attention on four key Herbig Ae/Be stars to understand the structural pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(39 citation statements)
references
References 109 publications
4
35
0
Order By: Relevance
“…The relatively low level of nearinfrared emission in HAe disks suggest that most have inner regions that are relatively empty of dust (Yasui et al 2014), an interpretation which is confirmed for the disks that have been directly imaged in scattered light (Fukagawa et al 2006), polarised light (Quanz et al 2012) or submillimetre emission (Brown et al 2012). While group II sources tend to have larger grains than those in group I, group II disks are not necessarily at a later evolutionary stage, since there is also a high incidence of transition disks in group I (Maaskant et al 2013).…”
Section: Disks Around Herbig Ae Starsmentioning
confidence: 76%
“…The relatively low level of nearinfrared emission in HAe disks suggest that most have inner regions that are relatively empty of dust (Yasui et al 2014), an interpretation which is confirmed for the disks that have been directly imaged in scattered light (Fukagawa et al 2006), polarised light (Quanz et al 2012) or submillimetre emission (Brown et al 2012). While group II sources tend to have larger grains than those in group I, group II disks are not necessarily at a later evolutionary stage, since there is also a high incidence of transition disks in group I (Maaskant et al 2013).…”
Section: Disks Around Herbig Ae Starsmentioning
confidence: 76%
“…Such spatially resolved mid-IR observations also provide an increase in the number of HAeBe disks with evidence for gaps, i.e., near discontinuous jumps in the radial density distribution (Panić et al, 2014;Matter et al, 2014). A correlation is emerging between the presence of gaps and the flared geometry of the disk (Maaskant et al, 2013). This is furthermore supported by near-IR scattered light images of the outer disk, where the group II disks are rather featureless, while the group I sources show the hallmarks of ongoing dispersal, like multiple spiral arms, disk gaps, pericentre offsets, and asymmetric shadowing of the outer disk favouring dynamical clearing by sub-stellar objects (see the overview by Grady et al, 2015).…”
Section: Disks In Intermediate-mass Ysosmentioning
confidence: 78%
“…Starlight impinges at a shallow angle on flat disks, and heating is inefficient compared to that above the same midplane location in a flaring disk. In addition, among the Herbig Ae/Be systems flaring, group I disks have resolved cavities or gaps 10-100 au scales in their millimetre dust emission (Maaskant et al 2013;Kama et al 2015).…”
Section: Observations and Samplementioning
confidence: 99%